Consumer Motivation in Developed Economies With Secular Stagnation - Callejas-Albiñana, Fernando Evaristo; de Vidales Carrasco, Irene Martín; Martínez-Rodríguez, Isabel; Isabel Callejas-Albiñana, Ana (Frontiers in Psychology, 2019)
In recent years, the slow pace of economic growth, high indebtedness and high unemployment registered in most developed economies since 2009 have revived the debate over the “secular stagnation hypothesis” first formulated by the neo-Keynesian economist Alvin Hansen in 1938. This return of the secular stagnation hypothesis occurred in November 2013, when Lawrence Summers postulated that the global economy was facing a scenario of low growth, low inflation, and a reduction in GDP per capita due to a chronic insufficiency of aggregate demand. The causes should be sought not only in cyclical factors associated with a long financial cycle and excessive accumulated public and private debt, but also in structural changes in the central economies in recent decades, linked to the rapid slowdown in population growth and the gradual aging of the population. Finally, other factors also depress demand, such as the progressive exhaustion of the globalization process and the consolidation of new labor models. In light of these developments, this paper’s aim is twofold: first, to perform an econometric panel-data study in order to determine the influence of each of these factors in explaining secular stagnation in recent years for the selected sample of countries; and, second, to lay out proposals for reorienting the government intervention strategies adopted since the onset of the financial crisis to promote consumption and achieve sustained growth, job creation, and poverty reduction.